Use of direct oral anticoagulants for postoperative venous thromboembolism prophylaxis after surgery for gynecologic malignancies. Issue 2 (6th January 2022) - Boo, Marilyn; Sykes, Peter; Simcock, Bryony
Abstract : Venous thromboembolism is a preventable cause of postoperative mortality in patients undergoing surgery for malignancy. Current standard of care based on international guideline recommends 28 days of extended thromboprophylaxis after major abdominal and pelvic surgery for malignancies with unfractionated heparin or low molecular weight heparin. Direct oral anticoagulants have been approved for the treatment of venous thromboembolism in the general population. This regimen has a significant advantage over other types of anticoagulation regimens, particularly being administered by non-parenteral routes and without the need for laboratory monitoring. In this review, we evaluate the role of direct anticoagulation and provide an update on completed and ongoing clinical trials.